UGC Curriculum and Credit Framework for PG Programmes, 2024 - Dr. H M Naveen (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The NEP 2020 strongly emphasises on multidisciplinary and holistic education. In response to this, the UGC has developed the Curriculum and Credit Framework for Post-graduate Programmes while considering the restructured degree programmes, entry and exit procedures, etc. the framework, which has no discipline-specific entry requirements and shows the credit structure and curriculum contents for both one-and two-year PG programmes, also offers an exit option at the end of the first year in two-year PG programmes. The framework is a testament to student empowerment, giving them freedom, flexibility and choices. According to the MoE and UGC, the re-structured degree programmes and promoted in both undergraduate and post-graduate education. In conformity with the re-structured undergraduate programmes, now the UGC has developed a Curriculum Framework for Post-graduate Programmes. The present article enlightens the HEIs regarding the recommendations of NEP 2020 relevant to Post-graduate Education ; main features of the PG Curriculum framework ; Credit Requirement and Eligibility for the PG Programme ; Generic Outcomes of Learning at the PG Level ; Graduate Attributes of PG Programmes ; Programme Designs, Curricular Components Credit Distribution ; Flexibility in changing subjects and lastly, Assessment Strategies.
Keywords: NEP 2020; PG Curriculum; PG Education; PG Curriculum & Credit Framework; Credit Distribution; Generic Outcomes; Programme Designs and Attributes; Flexibility